KORUPSI BIROKRASI PELAYANAN PUBLIK DI ERA OTONOMI DAERAH - Hadi, Kisno (Jurnal Penelitian Politik, 2016)
Todays big problem in Indonesian state enforcement and governmental system is corruption in both national and local level Corruption in public service bureaucracy can only be minimised if there is a hollistic and comprehensive understanding with in dimension network and background of corruption and some areas in public service bureaucracy that are highly touched by corruption Without this understanding efforts of corruption elimination in public service bureaucracy would be hard to achieve In order to support the process of corruption elimination in public service sector the role of public institutions that is built to control the execution of public service institution must be maximised therefore.